1993
DOI: 10.1016/0014-5793(93)80507-q
|View full text |Cite
|
Sign up to set email alerts
|

Differential shedding of the two subunits of the interleukin‐6 receptor

Abstract: cDNAs coding for the two receptor subunits of the interleukin-6 receptor have been stably expressed in Madine Darby canine kidney (MDCK) cells. The fate of the IL-6 binding protein (IL-6R) and of the signal transducing protein gpl30 was studied independently. Both proteins were proteolytically cleaved from cells metabolically labeled with [3"S]methionine/cysteine leading to the release of soluble receptor proteins of 55 kDa and 100 kDa, respectively. In contrast to the shedding of the ILdR gp130 was inefficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
84
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 118 publications
(87 citation statements)
references
References 36 publications
3
84
0
Order By: Relevance
“…Preliminary results show an induction of sOSMR, after a phorbol ester cell contact, that is counteracted by a metalloprotease inhibitor treatment. 4 This suggests that, in addition to the exon splicing mechanism, sOSMR can also be generated by proteolytic cleavage, similarly to that previously reported for the soluble IL-6R (43)(44)(45).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Preliminary results show an induction of sOSMR, after a phorbol ester cell contact, that is counteracted by a metalloprotease inhibitor treatment. 4 This suggests that, in addition to the exon splicing mechanism, sOSMR can also be generated by proteolytic cleavage, similarly to that previously reported for the soluble IL-6R (43)(44)(45).…”
Section: Discussionsupporting
confidence: 79%
“…Soluble IL-6 receptor is generated two different ways, shedding of the external IL-6R portion or alternative splicing, resulting in the secretion of a soluble form of receptor that lacks the transmembrane domain (43)(44)(45). Two large size signaling receptors belonging to the IL-6 family, gp130 and LIFR, have also been described as soluble products (38,46).…”
Section: Discussionmentioning
confidence: 99%
“…28 -30 Potential beneficial effects of early MMP-9 activation include removing matrix and necrotic myocytes, releasing growth factors and cell surface receptors, remodeling the extracellular matrix for scar formation, processing inflammatory mediators such as interleukin-1␤, and influencing angiogenesis. [31][32][33][34][35][36][37][38][39][40][41][42][43] An increase in MMP-9 that occurs within hours after reperfusion could serve a proactive function, with the overall result being an accelerated healing. The more focused secretion and activation of MMP-9 proposed here might obviate the danger of inappropriate proteolytic degradation.…”
Section: Functional Roles Of Mmp-9mentioning
confidence: 99%
“…No consensus amino acid sequence has been found at the proteolytic cleavage sites of cytokine receptor and growth factor precursors identified so far [1,2]. It was demonstrated that the presence or absence of the cytoplasmic domains of the IL-6R [3] and the p60 TNFR [4] had no effect on shedding of these two proteins, whereas in the case of the p80 TNFR [5] the intracellular part of the molecule influenced the generation of the soluble receptor. Furthermore it has been found that the Cterminal valine residue of the cytoplasmic tail of TGFcc is critical for the release of this growth factor [6].…”
Section: Introductionmentioning
confidence: 96%